EFFECT OF TEMPERATURE AND CONCENTRATION ON THE ABSORPTION OF SUGAR SOLUTION IN BENGKUANG (Pachyrrhizus erosus) - Malyan Afri Arlita; Sri Waluyo; Warji . (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2013)
Processing of foodstuffs mostly involves temperature and water. Interaction among the product, temperature and water changes the physical and chemical properties. The aim of this research was applying the Peleg’s equation to evaluate the effect of temperature and concentration of sugar solution on the absorption of sugar into bengkuang (Pachyrrhizus erosus). This research was designed at two different variables, which were temperature and concentration of sugar solution. The temperature was seted up at three levels : 30 oC, 40 oC and 50 oC, meanwhile the concentration was made at three levels : 20,6 oBrix, 30,7 oBrix and 40,7 oBrix. Three replications were conducted in each combination of the treatments along 450 minutes immersion duration. The results showed that the soaking temperatures affected to the absorption rate of sugar solution into bengkuang. The higher the soaking temperature the higher is the absorption rate. It was occurred the physical changes of bengkuang during soaking. The dimensions of the speciments decreased during immerse in the warm sugar solution. It may caused by water in the product comes out from the body. Furthermore, it proved that coefficient k1 of Peleg’s equation relates to temperature. The increasing of temperature was followed by decreasing of k1. At 30 oC and the concentration of 20,6 oBrix, the k1 is 0,254. It decreased become 0,124 at temperature of 50 oC. The decreasing of k1 was less with increasing of the concentration. Meanwhile, the coeffients k2 decreased with increasing of the concentration. At temperature of 30 oC and concentration of 40,7 oBrix, k2 is 19,76. It decreased become 14,11 at concentration of 40,7 oBrix. The decreasing of k2 was less with increasing temperature. Keywords: Bengkuang, immersion, temperature, sugar concentration, physical properties